Cultivo hidropônico de alface com água de reúso - Cuba, Renata da Silva (Universidade Federal de São Carlos, 2015)
The water for many years was considered inexhaustible, and only in recent decades, became aware of the shortage and the need to rationalize their use, look for ways to reuse and recovery of its quality. In this search context for reuse alternatives, the use of treated sewage sludge in agriculture can become an important tool in water management. Therefore this study evaluated the production of lettuce (Lactuca sativa L.) using hydroponic reuse water from sewage treatment plant. The experiment was conducted at Agricultural Science Center - UFSCar, in Araras, SP, in the greenhouse. Crops occurred from February to March (summer) and July-August (winter) 2014. The hydroponic system adopted was the Nutrient Film Technique (NFT), three treatments, with the first supply of water and fertilizers (TA ), the second with sewage treated and supplemented with fertilizers according to results of previous chemical analysis (TRA), and the third only treated sewage (TR), distributed in four randomized blocks. Each treatment consisted of four plots (stands), a 500 L tank for storing the nutrient solution, a motor pump assembly and a timer. Four polypropylene hydroponic profiles with 3 meters long were used in each bench, with 48 plants per plot, totaling 192 plants per treatment. We evaluated the fresh weight, nutritional status and the microbiological quality culture, and the amount of fertilizer used in the treatments. The fresh weights were subjected to analysis of variance and means compared by Tukey test at 5% probability. Only the TR treatment showed a significant difference compared to the other, in which the plants showed symptoms of deficiency and have significant reduction in fresh weight (p <0.01). There was no detectable presence of E.coli in any treatment, and it was possible to obtain a saving of fertilizers in some of TRA compared to TR. These results suggest the feasibility of reusing water application as a water source for hydroponics, with the necessary corrections, and that the hydroponic profile can act as a barrier to prevent contact of the effluent with the lettuce leaves, according to the conditions and care adopted in handling.
Keywords: Água - reutilização; Alface; Hidroponia; Efluente; Sustentabilidade; Lactuca sativa L.; Hydroponic; Nutrient solution; Effluent; Sustainability; CIENCIAS AGRARIAS